Sarojini Naidu as a Lyricist: A New Approach - Chouhan, Sandhya (Journal of Advanced Research in English & Education, 2021)
There are many women in India who have written poetry in English. Chief among them are Toru Dutt, Kamala Das and above all Sarojini Naidu. Her poems are praised not only in India, but all over the world. Her poetry is known for its powerful use of imagery, universal themes and above all lyricism. Due to her lyrcism, she was called “the Nightingale of India” by Mahatma Gandhi. How to cite this article: Chouhan S. Sarojini Naidu as a Lyricist: A New Approach. J Adv Res Eng & Edu 2021; 6(2): 10-11. DOI: https://doi.org/10.24321/2456.4370.202103